Side effects of insecticides alone or in a mixture with acaricide on life history traits and demographic parameters of Brevipalpus yothersi - Della Vechia, Jaqueline F. [UNESP]; Kapp, Ana Beatriz P. [UNESP]; Rocha, Claudiane M. [UNESP]; Andrade, Daniel J. [UNESP] (Systematic and Applied Acarology Society, 2023)
Brevipalpus yothersi is an important pest to citrus crop due to its ability to transmit the virus that causes citrus leprosis. The exposure of target and non-target organisms to different pesticides is a reality in field conditions. For successful management, it is essential to determine the effects of citrus commonly used pesticides on leprosis mites to determine how pesticides can interfere with the leprosis mite population. Therefore, this study aimed to evaluate the impact of insecticides, alone or associated with spirodiclofen, on B. yothersi life history traits and demographic parameters under laboratory and greenhouse conditions. Results suggest that cypermethrin and imidacloprid, both alone and in a mixture with spirodiclofen, phosmet in a mix with spirodiclofen and spirodiclofen alone did not interfere significantly in the fecundity and fertility of B. yothersi in laboratory conditions. In the same condition, only phosmet at 15.6, 125.0, and 250.0 mg.L-1reduced the fecundity of the mites. Brevipalpus yothersi population varied with the insecticide and mixture type in the greenhouse condition. Most insecticides and acaricide, alone or in a mixture, decreased pre-adult development, whereas female adult longevity was similar to control. Spirodiclofen combined with phosmet and imidacloprid decreased female adult longevity. Only spirodiclofen in a mixture with cypermethrin and phosmet alone did not interfere significantly with the intrinsic rate of population increase. The other insecticides and mixtures reduced that parameter. The mean time of one mite generation was decreased when the mites were exposed to all insecticides and acaricide combinations, spirodiclofen and phosmet alone. Therefore, cypermethrin, phosmet, imidacloprid, and spirodiclofen, alone or in a mixture, negatively impacted the development time and demographic parameters of B. yothersi.
Keywords: Citrus leprosis mite; Life table parameters; Non-target effect; Pesticide mixture; Spirodiclofen; Sublethal effect